Interdisciplinary Approaches in Doctoral and Higher Research Education: An Integrative Scoping Review - Kritika Rana; Sarah J. Aitken; Ritesh Chimoriya (Education Sciences, 2025)
Interdisciplinary approaches are increasingly integral in doctoral and higher research education, addressing complex global challenges through collaborations across disciplines. This review investigates the benefits, challenges, and educational impact of interdisciplinary approaches in doctoral research. This scoping review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and uses an integrative narrative synthesis. The review was conducted using four major academic databases (ERIC, PubMed, Scopus, and Web of Science) with an exploratory search using keywords related to interdisciplinary approaches, doctoral studies, and academic collaborations. The review synthesized evidence from studies published in English, focusing on interdisciplinary research in doctoral education, with no restrictions on study design. Eligibility criteria were based on the SPIDER tool (Sample, Phenomenon of Interest, Design, Evaluation, Research Type). The search was completed on 25 September 2024. The initial search retrieved n = 954 articles, with n = 167 articles being reviewed for the integrative synthesis. The review included studies that examined interdisciplinary collaborations in doctoral research, highlighting the benefits such as skill versatility, career readiness, and research adaptability. The challenges discussed included academic culture differences, communication barriers, and institutional silos. The role of academic institutions and supervisors in supporting interdisciplinary research through fostering collaborative environments was emphasized. The review provides insights into how interdisciplinary approaches can enhance doctoral education, preparing graduates to tackle global challenges. It highlights the need for improved integration of interdisciplinary practices in doctoral research and outlines future directions for fostering interdisciplinary collaborations in higher education.